AN EXPERIMENTAL INVESTIGATION OF THE EFFECT OF MASS FLOW RATES ON THE PERFORMANCE OF FLAT-PLATE SOLAR WATER HEATING SYSTEM USING CuO/WATER NANOFLUID - Joseph Stalin, P.Michael; Arjunan, T.V.; Sadanandam, N. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
One of the effective ways of increasing the efficiency of flat plate solar collector is to utilize nanofluids which are having high thermal conductivity. In the present study, an attempt is made to investigate the effect of mass flow rates on the performance of flat plate solar collector using CuO/water nanofluid. The experimental set up consists of flat plate solar collector; storage tank and ladder type heat exchanger. The instantaneous efficiency of solar collector is calculated by taking lower volume fraction of 0.01% with average particle size of 30 nm and varying the flow rate from 1 lpm to 3 lpm, as per ASHRAE standard, with and without Triton X-100 surfactant. The experimental results reveal that utilizing the nanofluid with mass flow rate at 1.5 lpm increases the collector efficiency by 19.7%.Â 